1996
DOI: 10.1002/(sici)1096-9063(199608)47:4<327::aid-ps432>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the New Herbicide KIH-6127. Part II. Synthesis and Herbicidal Activity of 6-Acyl Pyrimidin-2-yl Salicylates and Analogues against Barnyard Grass

Abstract: The method reported previously (Part I) was employed to prepare a variety of novel 6-acylsalicylates as key intermediates. 6-Acylpyrimidin-2-yl salicylates (2-acyl-6-[(4,6-disubstituted pyrimidin-2-y1)oxylbenzoate derivatives: Type l), the closely related phthalide compounds (3-alkyl-7-[(4,6-dimethoxypyrimidin-2-yl)oxy]phthalide derivatives : Type 2) and the ketal derivatives of 2-acyl-6-[(4,6-dimethoxypyrimidin-2-yl)oxy]benzoates (Type 3) were synthesized and their herbicidal activities measured. Methyl 2-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…We observed that, in general, all the ketal esters II , IIb , IIc and IA (R 4 = OR) are far less sensitive to acid‐ or base‐catalysed hydrolysis than the corresponding ortho ‐acetyl salicylates IX, IXa and their 6‐acyl‐pyrimidin‐2‐ylthiosalicylate derivatives A ′ that can undergo self‐catalysed rearrangement merely on standing to give the corresponding phthalide forms II , IIb , IIc and IA (R 4 = alkoxy) 8. 9, 27 The 6‐acylsalicylic acids IX (R = H) and the free acid derivatives A ′ (Figs 1 and 3; R = H) are generally isolated as the corresponding 3‐hydroxyphthalide forms IVb , IVc , II (R 4 = OH) and IA (R 4 = OH), as was shown by Finkelstein et al 29 for 3,7‐dihydroxy‐3‐methylphthalide II (R 3 = Me, R 4 = OH).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We observed that, in general, all the ketal esters II , IIb , IIc and IA (R 4 = OR) are far less sensitive to acid‐ or base‐catalysed hydrolysis than the corresponding ortho ‐acetyl salicylates IX, IXa and their 6‐acyl‐pyrimidin‐2‐ylthiosalicylate derivatives A ′ that can undergo self‐catalysed rearrangement merely on standing to give the corresponding phthalide forms II , IIb , IIc and IA (R 4 = alkoxy) 8. 9, 27 The 6‐acylsalicylic acids IX (R = H) and the free acid derivatives A ′ (Figs 1 and 3; R = H) are generally isolated as the corresponding 3‐hydroxyphthalide forms IVb , IVc , II (R 4 = OH) and IA (R 4 = OH), as was shown by Finkelstein et al 29 for 3,7‐dihydroxy‐3‐methylphthalide II (R 3 = Me, R 4 = OH).…”
Section: Methodsmentioning
confidence: 99%
“…These were then coupled with the pyrimidines IIIa at moderate temperatures (45–65 °C) to give the pyrimidinylmercaptophthalides IA (Figs 1 and 4; X = S, R 1 = R 2 = OMe), for example CGA 279 233 ( 37 ) and its 3‐hydroxy analogue 42 . The 3‐hydroxyphthalides IA (X = S, R 4 = OH), such as 42 , could then be transformed into further phthalide compounds IA (R 4 ≠ OH), such as 37, 43–47 , or into the alkylidenephthalides IB (X = S), or into known or still novel compounds of the type A ′ (X = S)7, 9, 32 (Figs 1, 4 and Table 1). The compounds IA (X = S) may be oxidized into the corresponding sulfoxides or sulfones IA (X = S(O), S(O) 2 ) 33…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations